Radiological Changes in Leprosy Patients With Disabilities and Deformities of Hands and Feet - Sharma, Sunakshi; Malgotra, Vikas; Wani, Mashkoor (Scripta Medica, 2024)
Background/Aim: Leprosy (Hansen’s disease) affects the skin and nerves. Hands and feet are commonly involved in all types of leprosy often leading to deformities. This study explored radiological changes in leprosy patients with hand and foot disabilities/deformities. Methods: Observational retrospective study was the chosen design. Study was conducted on 50 leprosy patients presenting at a tertiary care hospital with hand and foot disabilities during 2020-2022. Leprosy types were clinically diagnosed, confirmed by acid-fast bacilli staining. Bacteriological index (BI) and morphological index (MI) were calculated via Ridley’s scale. Histopathological examination of the skin lesions was also conducted. Radiological exams, anteroposterior and lateral X-rays, identified specific/non-specific bone changes. Results: Mean age was 38.8 years, bone changes identified at 40.3 years. Radiological changes were seen in 42.0 % patients (34 % patients had non-specific and 16 % had specific changes). These changes were seen more common and earlier in females as compared to males, the difference however was not significant (p = 0.6). Mean BI (2.8) and MI (32 %) of the patients with bone changes were slightly higher than those without bone changes but the differences were not statistically significant (2.2 and 27 %) (p = 0.2). Common specific changes were periostitis and subarticular erosion while osteopenia and phalangeal resorption were the most common non-specific changes. Conclusion: Non-specific bone changes were more common than specific ones and in females as compared to males. Lepromatous leprosy (LL) was associated with maximum bone changes with varied involvement in other types of leprosy.